PRIMARY SCHOOL TEACHERS’ PERCEPTIONS OF AND PRACTICES IN THE SELECTION AND DEVELOPMENT OF ENGLISH LEARNING MATERIALS - Nurdin Noni (LITERA, 2016)
PRIMARY SCHOOL TEACHERS’ PERCEPTIONS OF AND PRACTICESIN THE SELECTION AND DEVELOPMENTOF ENGLISH LEARNING MATERIALSNurdin NoniFBS Universitas Negeri Makassaremail: nurdinnoni@yahoo.comAbstractThis study aims to describe: (a) teachers’ profiles, (b) teachers’ perceptions of the use oflearning materials, and (c) practices in the selection and development of English learningmaterials by primary school teachers in Makassar City. The study used the descriptivemethod by involving primary school teachers of English. The sample consisted of 15primary school teachers of English, randomly selected from two clusters, namely thecity center and the suburb. The data were collected using a questionnaire. The resultsand discussion include the English teachers’ profiles, perceptions of, and practices in theselection and development of English learning materials for primary schools. In general,it can be concluded that the perceptions of primary school teachers of English are in linewith their practices in the selection and development of learning materials.Keywords: perception and practices, selection and development of English learningmaterialsPERSEPSI DAN PRAKTIK GURU SEKOLAH DASARDALAM PEMILIHAN DAN PENGEMBANGAN MATERI PEMBELAJARANBAHASA INGGRISAbstrakPenelitian ini bertujuan mendeskripsikan: (a) profil guru, (b) persepsi guru terhadappenggunaan materi pembelajaran, dan (c) praktik pemilihan dan pengembangan materipembelajaranbahasa Inggris oleh guru sekolah dasar di Kota Makassar. Metode yangdigunakan adalah metode deskriptif dengan melibatkan 15 guru bahasa Inggris sekolahdasar yang dipilih secara acak dari dua klaster, yakni pusat kota dan daerah pinggirankota. Data dikumpulkan dengan menggunakan angket. Hasil dan pembahasan meliputiprofil guru bahasa Inggris, persepsi, dan praktik pemilihan dan pengembangan bahanajar bahasa Inggris untuk sekolah dasar. Secara umum dapat disimpulkan bahwa persepsiguru bahasa Inggris sekolah dasar memiliki kesesuaian dengan praktik yang merekalakukan dalam pemilihan dan pengembangan bahan ajar.Kata kunci: persepsi dan praktik pembelajaran, pemilihan dan pengembangan materipembelajaranand setting